APPLICATION OF GOOD CORPORATE GOVERNANCE RELATING TO SHAREHOLDER, COMMISSIONER AND DIRECTORS OF LIMITED LIABILITY COMPANY IN INDONESIA - Sihabuddin (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2022)
Good corporate governance is the shareholder positioning in which contains specification to oblige shareholder participation. Global era and free market require new paradigm in carrying out business activity, how corporation can create positive image to their stakeholder. One of methods to do is to apply principles of good corporate governance. Corporation is one of the main pillars in modern social activity, because it is one of the centers of human activity to live their daily life. Corporation is important because of its significant contribution as source of public income, particularly in the tax sector. In limited liability Company, it is required good role of shareholder, commissioner and management (board of directors). Corporation is also a vehicle for channeling labor force.